CANNABIS SATIVA: A SYSTEMATIC REVIEW OF PLANT ANALYSIS - Bruna Tassi Borille; Marina González; Luiza Steffens; Rafael Scorsatto Ortiz; Renata Pereira Limberger (Drug Analytical Research, 2017)
Background: Cannabis has been the most widely used illicit drug worldwide throughout many years. Reports from different countries indicate that the potency of cannabis preparation has been increasing, as well as the ratio of tetrahydrocannabinol/cannabidiol has been changing. The high consumption along with the changing chemical profile of the drug has led increasingly to the interest in researching the cannabis plant. Methods: This article reviews available literature on the analytical methods currently used for the detection and quantification of cannabinoids in cannabis plant. The papers were screened by two researchers independently and following a pre-specified protocol. Results and Discussion: The systematic review of the literature allowed to include 42 citations on cannabis plant analysis. Conclusions: The analytical methods for cannabis material published in the included articles of this systematic review showed a lack of relevant information of the development of methods on GC and LC analysis and the limits of detection and quantification of mass detectors.